A Case of Tick-Borne Paralysis in a Traveling Patient. (27th June 2019) - Ha, Kevin; Lewis, Kathryn; Patel, Vandan; Grinceri, Jennifer
Abstract : Background . Tick paralysis is a neurotoxic tick-borne illness that causes ascending paralysis and may lead to respiratory failure. Patients often undergo extensive testing and prolonged hospitalization before the proper diagnosis is reached. Case Presentation . An 88-year-old man with dementia and dyslipidemia presented with new onset gait instability and was admitted for suspected cerebellar stroke. Exam was significant for the inability to perform tandem gait. Investigations included comprehensive metabolic panel, complete blood count, and noncontrast CT scan; none of them found any evidence of acute pathology. Two days into admission, a tick with surrounding erythema was found on the patient's left lateral chest during bathing. Dramatic improvement in truncal ataxia was noted following tick extraction. Discussion . Clinical suspicion of tick paralysis is often low due to the rarity of the condition. Although it is imperative to rule out acute cerebral or cerebellar pathology, a thorough skin examination should be performed on admission in any patient with new onset ataxia and ascending paralysis. This can lead to early diagnosis, conservation of resources, and the avoidance of subjecting patients to invasive testing.